Village Policy Reform through Law No. 3 of 2024: Village Head Tenure and the Role of Rehabilitation Funds - Marta, Dwi Jati (Ministry of Home Affairs, 2025)
Village policy reform in Indonesia underwent significant changes with the enactment of Law No. 3 of 2024, which regulated the village heads’ term of office and the management of rehabilitation funds. This study employed a descriptive qualitative method with a normative legal approach to analyze the reforms introduced by Law No. 3 of 2024, particularly the extension of the village head’s term of office and the role of rehabilitation funds. Legislative analysis, literature review, and content analysis were employed, and source triangulation was applied to ensure validity and generate insights into policy effectiveness and recommendations for improved village governance. It also examined the impact of these reforms on sustainable development and disaster resilience. Utilizing the frameworks of good governance and participatory governance theories, this study highlighted the risks of power abuse, the importance of transparency, and community participation in village fund management. A comparative case study approach was adopted to provide policy recommendations to enhance accountability, prevent corruption, and improve village governance effectiveness.